2015
DOI: 10.1021/jacs.5b10321
|View full text |Cite
|
Sign up to set email alerts
|

Conjugation between σ- and π-Aromaticity in 1-C-Arylated Monocarba-closo-dodecaborate Anions

Abstract: Conjugation between σ- and π-aromatic moieties in 1-C-arylated monocarba-closo-dodecaborate anion derivatives 2 has been identified by means of kinetic experimental studies combined with theoretical calculations. We found that the reaction rate of iodination at the 12-B vertex of the carborane anion cage was affected by distal substituents on the benzene ring connected at the antipodal carbon vertex. Hammett and Yukawa-Tsuno plots indicated that substantial resonance effects are involved. Density functional th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…35 It has to do with the extra stability or instability of a cyclic yet planar structure because of the additional delocalization of electrons, 6 either π or σ, leading to the redistribution of the electron density of the system. 710 The controversy about aromaticity lies in the fact that many different categories of aromaticity have been unveiled in the literature, 3,11,12 lots of descriptors to characterize it have been proposed as well, 13 but there exists no single descriptor that can be used as the general quantitative measure. 14 The culprit is the fact that these descriptors are often measures of one property only from its many manifestations of the phenomenon, such as energetics, 6 geometry, 3 ring current, 15 and so forth, which are the consequences of the aromaticity phenomenon, not its root cause.…”
Section: Introductionmentioning
confidence: 99%
“…35 It has to do with the extra stability or instability of a cyclic yet planar structure because of the additional delocalization of electrons, 6 either π or σ, leading to the redistribution of the electron density of the system. 710 The controversy about aromaticity lies in the fact that many different categories of aromaticity have been unveiled in the literature, 3,11,12 lots of descriptors to characterize it have been proposed as well, 13 but there exists no single descriptor that can be used as the general quantitative measure. 14 The culprit is the fact that these descriptors are often measures of one property only from its many manifestations of the phenomenon, such as energetics, 6 geometry, 3 ring current, 15 and so forth, which are the consequences of the aromaticity phenomenon, not its root cause.…”
Section: Introductionmentioning
confidence: 99%
“…We found that the reaction rate was affected by distal substituents on the benzene ring connected at the antipodal carbon vertex. Hammett and Yukawa–Tsuno plots indicated that substantial resonance effects are involved (Figure ) …”
Section: Recent Advances In Synthetic Chemistry At the Carbon Vertex:mentioning
confidence: 99%
“…Hammett and Yukawa-Tsuno plots indicated that substantial resonance effects are involved (Figure 8). [18] Furthermore, density functional theory (DFT) calculations at the B3LYP/6-31 + G* level revealed ar ather strong orbital interaction between one of the degenerate HOMO-1so f1 and one of the HOMOs of the benzene ring 19 (shownw ith red lines). Out-of-phase interaction at the carbon vertex forms the HOMO of 10 a,w hich appears to show a p-conjugation-like interaction over the whole molecule, while the in-phase interaction provides the more stable HOMO-5 ( Figure 9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ) is a spherical compound formed by one or more boron peaks of polyhedral boron compounds, which is formed by carbon atoms. The volume is similar to that of a benzene ring [ 1 5 ]. This is a special large steric skeleton with a very strong hydrophobic structure.…”
Section: Introductionmentioning
confidence: 99%